Produk Makanan Keripik Berbasis E-Commerce untuk Meningkatkan Promosi UMKM di Kecamatan Tanjung Mutiara - Sartiva, Yola; Hasnah, Radiatul (JOVISHE : Journal of Visionary Sharia Economy, 2023)
The problem faced in this research is the limited promotion of local food products, especially chips produced by MSMEs in Tanjung Mutiara District. This is due to the low utilization of information technology and digital platforms in product marketing, so that the wider market potential cannot be maximized. To overcome these problems, this research aims to design and develop an OpenCart-based e-commerce platform that can help promote and market chip products. With this platform, it is expected that MSME players can increase the visibility of their products, reach wider consumers, and ultimately increase business income significantly. To overcome these problems, this research uses the Research and Development (R&D) method with the 4-D development model (Define, Design, Develop, Distribute). The results showed that the OpenCart-based e-commerce platform developed successfully met the needs of MSMEs in promoting chip products in Tanjung Mutiara sub-district. Testing has proven that the platform is effective in significantly increasing product visibility, expanding market reach, and accelerating transactions. In addition, user response to the platform is very positive, with most entrepreneurs stating that the system helps them save time and costs in marketing activities. The findings of this study are that the design of an OpenCart-based e-commerce platform can effectively help MSMEs in Tanjung Mutiara sub-district to improve the promotion and marketing of chip products.